Hubungan Pelaksanaan Standar Pelayanan Antenatal oleh Bidan di Desa dengan Kejadian Anemia di Kabupaten Purworejo - Anita Lontaan, Djaswadi Dasuki, Ova Emilia (Berita Kedokteran Masyarakat (BKM), 2003)
Background: It is estimated that 20.000 Indonesian women die annually due to ob-stetric complication. Bleeding, preeclampsia or eclampsia and infection were found to be the major causes of maternal death. This maternal death can be effectively pre-vented if communities are well informed about emergency signs as well as the provi-sion of qualified health service in primary care.Objectives: This study was conducted to know the relationship between implementa-tion of antenatal service standard done by village midwife and the incidence of ane-mia.Methods: This was an observational study with historical cohort design. Two methods were used: quantitative methods to examine the effect of antenatal service standard implementation on the incidence of anemia.The subjects were interviewed after having antenatal service. Qualitative method was used to confirm the study results by doing focus group discussion in which midwives from primary health care of Purworejo and Kutoarjo involved. The group discussion was focused on the implementation of antena-tal service standard according to Department of Health 2000. Data were analyzed us-ing univariate, bivariate, stratification, and multivariate analysis. Qualitative data were analyzed using thematic analysis.Results: The result showed that pregnant mothers who received non-standard antena-tal service had risk of anemia with OR=3.404 (95% CI: 1.303